1981
DOI: 10.1016/s0022-5347(17)55149-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mitomycin C on Superficial Bladder Cancer

Abstract: A course of intravesical mitomycin C, consisting of 8 weekly doses of 30 or 40 mg., was evaluated in 16 patients with superficial bladder cancer (stages O and A). Cystoscopically documented tumor was destroyed completely in 11 patients (69 per cent), while 3 patients exhibited partial tumor regression. Two patients had only multifocal, grade 3 carcinoma in situ and both had a complete response with negative biopsies and cytology at the 12-week evaluation. Toxicity was minimal. Further data, including longer fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

1984
1984
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(17 citation statements)
references
References 7 publications
0
16
1
Order By: Relevance
“…In our opinion, contact exanthema is ow ing to inhygienic handling, while general exanthema can be seen as a result of allergic reactions. Complications observed after intravesical MMC, as described pre viously by Bracken et al [1980] and Soloway et al [1981], cannot be explained by resorption of unchanged MMC which might take place during completion of ther apy. It cannot be excluded that MMC metabolites and/or degradation products are responsible for rare severe tox icity, such as bone marrow suppression.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In our opinion, contact exanthema is ow ing to inhygienic handling, while general exanthema can be seen as a result of allergic reactions. Complications observed after intravesical MMC, as described pre viously by Bracken et al [1980] and Soloway et al [1981], cannot be explained by resorption of unchanged MMC which might take place during completion of ther apy. It cannot be excluded that MMC metabolites and/or degradation products are responsible for rare severe tox icity, such as bone marrow suppression.…”
Section: Discussionmentioning
confidence: 92%
“…The use of intravesical chemotherapy with MMC either for treatment of superficial bladder cancer or for prophylaxis following transurethral resection has been gaining popularity in the last decade, after favourable reports from Mishina et al [1975Mishina et al [ , 1982, Mishina and Watanabe [ 1979], Soloway [ 1980], Soloway et al [ 1981 ], Prior et al [ 1982], Harrison et al [1983] and Somerville et al [1985]. Systemic toxic side-effects from intravesi cal MMC are generally low, and life-threatening sideeffects were not observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is due to many factors, including continuous exposure of the bladder epithelium to carcinogens, multifocal growth of tumors, implantation of tumor cells during TUR and incomplete tumor resection [1,9,10]. For these reasons, intravesical chemotherapy and immunotherapy have been advocated for patients at high risk of recurrence and progression [3][4][5][6]11]. The agents which have been most commonly used for bladder instil- lation are thiotepa, mitomycin C, doxorubicin and BCG [6].…”
Section: Discussionmentioning
confidence: 99%
“…As evidenced by several studies, the various agents in use can reduce the rate of tumour recurrence. Controlled clinical trials have shown that, following chemotherapy, the rate of tumour recurrence is reduced by 16-18%, immunotherapy achieved a complete response in about half of the patients with papillary tumours and over 70% in those with carcinoma in situ (Koontz et al, 1981;Schulman et al, 1982;Garnick et al, 1984;Soloway et al, 1981;Herr et al, 1989). Of more importance is the impact of intravesical therapy on tumour progression and patient survival in superficial bladder cancer.…”
Section: Discussionmentioning
confidence: 99%